Analisis Determinan Pencegahan Fraud Pengelolaan Dana Desa dengan Moralitas sebagai Moderasi - Putri, Hanah Ladhinah; Yuliani, Nur Laila; Mranani, Muji; Anisa, Friztina (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: This study aims to test empirically and analyze the effect of competence, internal control systems, religiosity, and whistleblowing on fraud prevention in managing village funds with morality as a moderating variable. Method: The research sample was village officials in Secang District, Magelang Regency using the purposive sampling method and obtained 78 respondents, while for testing the hypothesis using moderated regression analysis. Results: The results showed that competence had a positive effect on fraud prevention in managing village funds and religiosity had a negative effect on fraud prevention in managing village funds. Meanwhile, the internal control system and whistleblowing have no effect on fraud prevention in managing village funds. Morality strengthens the influence of religiosity on fraud prevention while morality weakens the influence of competence on fraud prevention in village fund management. However, morality does not moderate the influence of internal control system variables and whistleblowing on the prevention of village fund management fraud. Implications: This research is expected to add to knowledge, insight, and empirical evidence and can be a reference for further research on fraud prevention in village fund management. In addition, it is hoped that this will provide additional information and input to encourage the Village Government to improve fraud prevention in managing village funds Novelty: This research builds on previous research by adding a whistleblowing variable which is expected to improve performance and prevent fraud.